Faktor-Faktor yang Mempengaruhi Wanita Menikah Berusia Produktif untuk Bekerja Tahun 2019 (Studi Kasus Provinsi Jawa Barat) - Nur Siti Annazah (Jurnal Ketenagakerjaan, 2021)
The population growth of both men and women from year to year shows that the supply of labor in Indonesia has increased every year. The occurrence of this increase also indirectly affects the increase in the number of the workforce. The role of women is basically taking care of the household. However, there are several conditions that encourage women to continue working. Women's Labor Force Participation Rate (TPAK) has always increased every year. This study aims to examine the factors that influence the decision of married women of productive age to work. Using sample data from SAKERNAS in August 2019. The data were analyzed using logistic regression analysis. The dependent variable was the working status of married women. Meanwhile, the independent variables were the number of household members, latest diploma held or level of education, and age of married women. The results of the study show that the three variables significantly influence the decision of married women to work. The variables of the number of family members and age have a negative effect on the decision of married women to work. Meanwhile, the education level variable has a positive effect on the decision of married women to work.